Nigericin is effective against multidrug resistant gram-positive bacteria, persisters, and biofilms - Zhu, Xiaoli; Hong, Anjin; Sun, Xihuan; Wang, Weijie; He, Guanghui; Luo, Huan; Wu, Zhenhua; Xu, Qingyan; Hu, Zhiyu; Wu, Xiaobing; Huang, Donghong; Li, Li; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Multidrug-resistant (MDR) bacteria pose a significant clinical threat to human health, but the development of antibiotics cannot meet the urgent need for effective agents, especially those that can kill persisters and biofilms. Here, we reported that nigericin showed potent bactericidal activity against various clinical MDR gram-positive bacteria, persisters and biofilms, with low frequencies of resistance development. Moreover, nigericin exhibited favorable in vivo efficacy in deep-seated mouse biofilm, murine skin and bloodstream infection models. With Staphylococcus aureus, nigericin disrupted ATP production and electron transport chain; cell death was associated with altered membrane structure and permeability. Obtaining nigericin-resistant/tolerant mutants required multiple rounds of challenge, and, cross-resistance to members of several antimicrobial classes was absent, probably due to distinct nigericin action with the GraSR two-component regulatory system. Thus, our work reveals that nigericin is a promising antibiotic candidate for the treatment of chronic or recurrent infections caused by gram-positive bacteria.